Structure-activity studies of dodecatungstophosphoric acid impregnated bentonite clay catalyst in hydroxyalkylation of p-cresol - Garade, Ajit C.; Kshirsagar, V. S.; Jha, Ajay; Rode, C. V. (Catalysis Communications, 2010)
Bentonite clay impregnated with dodecatungstophosphoric acid (20% DTP/BNT) showed an excellent activity, selectivity and stability [95% product yield with 94% selectivity to 2, 2'-methylenebis (4-methylphenol), DAM] for the hydroxyalkylation of p-cresol with formaldehyde at 353 K and for a mole ratio of 5. Ammonia-TPD results showed that an increase in total concentration of acid sites from 4.9 of parent bentonite to 11.6 micromoles per surface area NH(3) (mu molS(-1) NH(3)) of 20% DTP/BNT was due to a strong interaction of protons of bulk DTP with surface hydroxyl groups of BNT as evidenced by (31)P NMR studies. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: (31)P CPMAS NMR; Bentonite; Hydroxyalkylation; p-Cresol; surface modification

Solvothermal synthesis of mesoporous manganese oxide with enhanced catalytic activity for veratryl alcohol oxidation - Jha, Ajay; Chandole, Tejansh; Pandya, Rajan; Roh, Hyun-Seog; Rode, Chandrashekhar V. (RSC Advances, 2014)
Catalyst activities of manganese and cobalt oxides prepared by solvothermal and co-precipitation methods were studied for veratryl alcohol oxidation. Manganese oxides showed higher activity performance than that of cobalt oxides irrespective of the method of preparation. The solvothermal method yielded mesoporous manganese oxide without using any template giving mixed phases of monoclinic Mn5O8 and hausmannite Mn3O4. The mesoporous manganese oxide exhibited excellent activity for liquid phase aerobic oxidation of veratryl alcohol under base free conditions, with 90% conversion and almost complete selectivity towards veratraldehyde. The detailed characterization results on morphology, size and composition of the prepared mesoporous manganese oxide obtained by XRD, XPS, H-2-TPR, N-2 adsorption-desorption isotherms, FESEM and HR-TEM techniques were used to understand the role of morphological and structural features in enhancement of the observed catalytic activity.